(untitled) (Fiep Bulletin - online, 2013)
The present study evaluates and discusses the association between the use of exercises multiarticulars in the series of the practising beginners and practising that sport, in the vision of the professional of Physical Education for motor coordination. The methodology adopted was of descriptive stamp, with typology of international questionnaire of level of physical activity (IPAQ - version 6 with adaptation for motor performance) : pilot study in Brazilian adults and youths, with 68 professionals of different towns filling the questionnaire. The result for analysis is in graphics where are presented the answers of the professionals of Physical Education, that show a vision hurried about exercises multiarticulars in the motor performance according to scientific literatures of the branch. It observed itself in the graphic statistical that 42% of the professionals of the Rio de Janeiro, 27% of Niterói and 31% of São Gonçalo are going to have a good standard of knowledge regarding the motor coordination for the activities multiarticulars, however in the academies of Niterói and São Gonçalo was not observed a methodological stardandization of training, that provides a specific increase of that physical quality involved. Established itself the utilization of the exercises multiarticulars for the need of evolve the motor coordination in the conception of the Professionals of Physical Education.